PERAN GURU DALAM IMPLEMENTASI NILAI ING NGARSO SUNG TULODHO UNTUK MEMBANGUN BUDAYA POSITIF DI SMP NEGERI 1 KAJEN - Turiyah; Teguh Gunarso; Soedjono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to investigate the role of teachers in implementing the Javanese philosophy "Ing Ngarso Sung Tulodo" (being a role model) to cultivate a positive school culture at SMP Negeri 1 Kajen. Employing a qualitative descriptive approach, data was gathered through observations, interviews, and document analysis. The results reveal that the implementation of "Ing Ngarso Sung Tulodo" by teachers is pivotal in fostering a positive school environment. This underscores the central role of teachers in embodying these values. To effectively cultivate a positive culture, teachers need to comprehend their position and responsibilities. At SMP Negeri 1 Kajen, the implementation of "Ing Ngarso Sung Tulodo" is manifested through various practices, including strict adherence to attendance and effective classroom management, exemplary conduct and communication, and the ability to address student mistakes judiciously. Consequently, a positive school culture has emerged, characterized by a favorable perception of school values, the implementation of these values, collaborative efforts among teachers, and active involvement in school development.